PENGEMBANGAN MEDIA AUDIO VISUAL MATERI TARI PEGI MANTANG DI KELAS VIII B SMP NEGERI 1 TUNGKAL ILIR BANYUASIN - Duwi Mutiara; Hasan; Evita Elvandari (Universitas Hamzanwadi, 2025)
Learning at SMP Negeri 1 Tungkal Ilir already has media that can be used to support the learning process, but in the subject of art and culture there is no media that can support the learning process so that learning art and culture, especially dance, is less popular with students. With the existence of research and development / R & D procedures used by researchers include 5 stages, namely using the ADDIE model (Analyze, Design, Develop, Implement, and Evaluate). The use of the results of this product was carried out in class VIII B with a total of 24 students in one class. Before the media is tested on students, the media must first pass a validation test carried out by three validators from the fields of art, media, and language. Based on the results of the practicality test of the dance tutorial video by distributing student response questionnaires during the learning process, an average score of 85-95 was obtained, which was categorized as students understanding the Pegi Mantang dance learning tutorial video. So it can be concluded that this learning video can make it easier for students in the learning process.